Verbal Orders Don't GoWrite It!: Building and Maintaining the Promised Land - Shearer, Heather (Nova religio, 2018)
Peoples Temple achieved impressive objectives as an organization, the most impressive of which was establishing and maintaining an agricultural communitythe Promised Landin the remote jungle of Guyana. An activity theory analysis of work oriented to the Promised Land reveals that textseveryday genres such as forms and listswere important tools used by the group to achieve this objective. A study of these textual tools helps us to understand how Peoples Temple was able to meet its collective organizational goals and how individual members achieved personal transformations within the organization. Examining the group's textual practices adds depth to existing studies of Temple history by showcasing the efficacy of organizational labor that members themselves might have taken for granted. In addition, this methodological approach provides a view of Peoples Temple work unencumbered by the social problems paradigm, offering instead an approach that is compatible with a social possibilities paradigm.